Pengembangan LKPD Berbasis STEM di Sekolah Dasar - Nurul Saadah Agustina; Novi Yanthi (Postgraduate, University of Mataram, 2023)
To develop students’ 21st century skills, it is necessary to develop STEM-based worksheet to provide learning that links knowledge and technology with contexts in everyday life so as to create learning that is able to prepare students to compete in the future. The main focus of this research is the development of a feasible STEM-based worksheet in science education in elementary school. This research is a Design and Development study with the ADDIE model which consists of the analysis, design, development, implementation and evaluation stages. Based on the analysis of the curriculum, needs, and the learning environment of students, STEM-based worksheet is developed. The worksheet was assessed for its feasibility by experts and teachers. In addition, user parents/guardians and students are given response assessments. The evaluation of experts and teacher practitioners shows that the teaching material is considered very suitable for use .